Breastfeeding Knowledge and Attitude Instrument: Validity and Reliability Testing Among Primiparous Mothers - Surtania; Anggorowati; Achmad Zulfa Juniarto (Indonesian Journal of Global Health Research, 2025)
Breast milk is widely recognized as the optimal source of infant nutrition, yet exclusive breastfeeding coverage remains below global and national targets. Maternal knowledge and attitudes, especially among primiparous mothers, are key determinants of breastfeeding practices. Therefore, valid and reliable instruments are essential to measure these factors accurately. Objective to develop and test the validity and reliability of questionnaires assessing knowledge and attitudes toward breastfeeding among primiparous mothers. This study applied a cross-sectional design involving 15 postpartum mothers with normal deliveries at RSUD Dr. Soewardi Kendal. Two instruments were tested: a 16-item knowledge questionnaire and a 15-item attitude questionnaire. Validity was assessed using Pearson’s correlation with r table = 0.514, and reliability was tested using Cronbach’s alpha. The knowledge questionnaire showed 12 valid items with a Cronbach’s alpha of 0.833, indicating good internal consistency. The attitude questionnaire produced 12 valid items with a Cronbach’s alpha of 0.861, reflecting excellent reliability. Both the knowledge and attitude questionnaires demonstrated strong validity and reliability, making them feasible instruments for assessing breastfeeding-related factors among primiparous mothers in future research.